Pola Komunikasi Ayah Tunggal Dengan Anak Pasca Perceraian Dalam Perspektif Family Communication Pattern Theory - Dyah kusumawati; Agustrijanto Agustrijanto (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
Single Fatherhood as a consequence of divorce creates distinctive relational and communicative challenges within post-divorce family dynamics. Changes in parental roles and living arrangements require fathers to renegotiate interaction patterns in order to maintain emotional bonds with their children. This study aims to identify and classify father–child communication patterns in post-divorce contexts based on Family Communication Patterns Theory (FCPT). A qualitative case study design with purposive sampling was employed, involving three single fathers as key informants. Data were collected through in-depth interviews and analyzed using the Miles and Huberman interactive model. The findings indicate that single fathers tend to construct communication characterized by openness, emotional responsiveness, and child-centered interaction strategies. Despite structural and emotional challenges following divorce, participants demonstrated adaptive communication practices that support relational continuity and emotional well-being. These findings contribute to the understanding of paternal communication roles within non-traditional family structures and highlight the importance of flexible communication orientations in maintaining healthy father–child relationships.